TEKNIK MENYUSUI YANG BENAR DITINJAU DARI USIA IBU, PARITAS, USIA GESTASI DAN BERAT BADAN LAHIR DI RSUD SIDOARJO: CORRECT BREASTFEEDING TECHNIQUES FROM MOTHER'S AGE, PARITY, GESTATION AGE AND BIRTH WEIGHT AT SIDOARJO Hospital - Rinata, Evi; Iflahah, Dini (Jurnal Kebidanan Midwiferia, 2015)
Breastfeeding is a natural process where nearly all mother can breastfeed her baby without help from others, but in fact not all mother can breastfeed with the correct technique of breastfeeding. Based on previous studies, in Primary Health Care of Waru, 75% breastfeed mothers with wrong technique. This research is analytic with cross sectional design, using the primary data and secondary data. The sampling using the probability sampling, with the simple random sampling technique. The sample used as much as 45 persons of breastfeeding mothers than 50 population. The data was presented in the form of the frequency tabulation and cross tabulation, and then was analyzed with the test of the chi-square and the fisher exact with α = 0,05. The result of this research showed maternal age ≥ 19 years old (93,3%), multipara (68,9%), level of education senior high school (44,4%), work as house wife (68,9%), pervaginam labour (57,8%) and cesarean section (42,2%), gestation age ≥ 37 weeks (93,3%) and birth weight ≥ 2500 grams (93,3%). Most of breastfeeding technique was incorrect (53,3%) and correct breastfeeding technique (46,7%). The majority of respondent has no breast problem (82,2%). There is statistically no relationship between maternal age (p=0,142), parity (2count=0,96), gestational age (p=0,142) and birth weight (p=0,142) with correct technique of breastfeeding.